A Review On The Interaction Component In Formulating Sustainable Supply Chain Management - Wan Mahmood, Wan Hasrulnizzam; Mohamed, Norhafiza; Muhamad, Mohd Razali; Yusup, Muhamad Zaki (Science International (Lahore), 2014)
-